Mechanization of transplanting and weeding for rice intensification (SRI) for improved paddy yield in Malaysia - Wan Ismail, Wan Ishak; Ibrahim, Bala; Suleiman, Samaila (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The overall objective of this research was to develop a new approach to increase paddy production with the limited resources input through management practices that simultaneously provide better growth condition. The study evaluated the management practice method known as System of Rice Intensification (SRI) using a modified Kubota Transplanter for planting of paddy and a modified high clearance weeder for crop maintenance. Main SRI management practices such as planting depth, missing hill, hill population, number of seedling per hill, soil characteristics of the sites, and moisture content and the frequencies of weeding were evaluated. The effects of different hill-spacings on 14-days old seedlings of MR219 rice variety were studied using analysis of variances. The experiment was designed at three seeding rates (70g, 75g and 240g) per tray. The plant characteristics at transplanting time consisted of 2 to 3 number of leaves, 2 mm stem thickness, 19 mm stem length and 3.5 mm root length. The planting parameter showed that increase in spacing resulted in more tillers and more panicle per plant, while hill population and sterility ratio increases with decrease in spacing. The study also evaluated the effect of levels of mechanical weeding using four different locally fabricated rotary weeders on the yield and vegetative components of rice under the System of Rice Intensification at Tanjung Karang Irrigation Scheme of Malaysia. Results indicated that wedding levels had a significant effect on vegetative paddy height with 60.05cm as the highest average vegetative height obtained at three levels of rotavations (mechanical weeding). The analysis of variance of the yield indicates a significant difference in yield with increase in the levels of mechanical weeding with 13.1tons/Ha being the highest obtained 30DAT.